PEDAGOGICAL LEADERSHIP ASPECTS OF LATVIAN VOCATIONAL EDUCATION INSTITUTIONS’ LEADERS - Pigozne, Tamara; Surikova, Svetlana; Fernandez Gonzalez, Manuel Joaquin; Medveckis, Arturs; Pigoznis, Aivars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Leadership of vocational education institutions’ leaders is one of the leading resources in order to provide access, quality, competitiveness and sustainability of vocational education. The goal of the research is to analyse leadership of vocational education institutions’ leaders on the basis of the Charismatic, Emotional, Anticipatory, Professional, Participatory, Cultural, Formative and Administrative Dimensions (Gento & González, 2012) identified due to the analysis of scientific literature and normative documents in the context of the vocational education reform. The outcomes of the quantitative research testify that students assess the vocational education institution leaders’ leadership more critically than staff, but from the respondents’ point of view the leadership characterizing criteria such as professionality, emotionality and charisma are assessed the highest in general.